Efficacy and safety of epaminurad, a potent hURAT1 inhibitor, in patients with gout: a randomized, placebo-controlled, dose-finding study - Jae-Bum Jun; Hye-Soon Lee; Sang-Hyon Kim; Seung-Geun Lee; Doo-Ho Lim; Jinhyun Kim; Yong-Beom Park; Mie Jin Lim; Seung-Jae Hong; Hyo-Jin Choi; Shin-Seok Lee; Hyun Ah Kim; et al. (Arthritis Research & Therapy)
Abstract Background Gout is the most common inflammatory arthritis. Current urate-lowering therapies have limitations, such as adverse drug reactions or limited efficacy. Epaminurad is a novel selective human urate transporter 1 (hURAT1) inhibitor that has been shown to reduce serum urate (sUA) levels in healthy volunteers and patients with gout. The aims of the current study were to evaluate the urate-lowering efficacy and safety of epaminurad compared with placebo in patients with gout, and to determine the optimal dose. Methods This multicenter, randomized, double-blind, placebo-controlled, dose-finding phase 2b clinical trial, which incorporated a standard-treatment reference arm, enrolled patients aged 19–70 years with gout and sUA level ≥ 0.42 mmol/L. Participants received gout prophylaxis and followed therapeutic lifestyle changes, and were randomized to receive epaminurad 3 mg, 6 mg or 9 mg, or febuxostat 80 mg, or matching placebo, once daily for 12 weeks. The primary efficacy endpoint was the proportion of patients with sUA level < 0.36 mmol/L at week 4 after initiation of study treatment. Statistical comparisons were performed between the epaminurad and placebo groups. Results Overall, 169 patients received study medication (99.40% male, mean ± SD age 48.26 ± 13.15 years, sUA level 0.53 ± 0.09 mmol/L). Mean adherence to treatment was > 90% in all groups. The proportion of patients with sUA < 0.36 mmol/L at week 4 was significantly higher in each epaminurad group (9 mg, 88.89%; 6 mg, 71.79%; 3 mg, 54.05%) compared with placebo (0.00%) (all p < 0.0001). The response rate in the febuxostat group was 84.21%. The proportion of patients who achieved sUA < 0.30 mmol/L, and mean percent and absolute change in sUA, were also significantly greater in all epaminurad groups versus placebo at week 4. Outcomes were consistent at weeks 8 and 12. The adverse event rate did not differ between epaminurad groups and placebo, and most events were mild. There were no significant differences in mean serum creatinine levels or liver function parameters between the epaminurad groups and placebo. Conclusions Epaminurad was effective at reducing sUA levels in patients with gout. The study also confirmed the safety and tolerability profile during 12 weeks of treatment. Trial registration ClinicalTrials.gov NCT04804111 (registered on 15 November 2020).